Respuesta :
√3x+1 −x+3=0
(√3x+1)^2 =(x-3)^2
3x + 1 = x^2 - 6x + 9
0 = x^2 - 9x + 8
0= (x - 8) (x – 1)
X = 8 and x = 1
First let’s solve for x = 8
√3 (8) + 1 – (8) + 3 = 0
√24 + 1 – 5 =0
√25 – 5 =0
5-5=0
0=0
X=8 is a solution
For x=1
√3 (1) + 1 – (1) + 3 = 0
√4 – 4 =0
2 – 4 =0
-2=0
X=1 is not a solution
Therefore:
a. There is only one solution: x = 8. The solution x = 1 is an extraneous solution.
Answer:
a. There is only one solution: x = 8. The solution x = 1 is an extraneous solution.
Step-by-step explanation:
took the test